Distribution of total heterotrophic bacteria (THB) and Vibrio parahaemolyticus in shrimp culture ecosystem - Dalmin, G; Purushothaman, A; Kathiresan, K (Indian Journal of Fisheries, 2011)
The populations of total heterotrophic bacteria (THB) and Vibrioparahaemolyticus were analysed in modified extensive shrimp (Penaeusmonodon) culture pond, located on the bank of Vellar estuary, Parangipettai,India, for ten months covering two consecutive culture operations. The microbialload in water, sediment and culture species was more in the first culturethan the second. The microbial load increased with the days of culture, mainlydue to the organic load in the pond environment, however, physico-chemicalparameters such as salinity, temperature, pH and dissolved oxygen were withinthe permissible limits throughout the culture. Sediments had more bacterialload than water and shrimps. A heavy load of THB (40% vibrios) and V.parahaemolyticus was observed in the first culture that faced a serious viraldisease problem (white spot disease) and mass mortality at the final stages ofculture. The bacteria might have acted as primary pathogen by facilitating theentry of viron particles as well as secondary pathogen, leading to mass mortalityof shrimps. Prophylactic measures, regular use of disinfectants and properpond bottom management have reduced bacterial load in second disease-freesuccessful culture operation.